Recurrent hepatic encephalopathy precipitated by urinary tract infection in patient with liver cirrhosis: a case report - Saraswati Seputra, Desak Putu Gayatri; Pralambari, Luh Putu Dea Sasmita; Suryana, Ketut (International Journal of Advances in Medicine, 2021)
Liver cirrhosis is a chronic liver injury marked by necro-inflammation and fibrogenesis. It is associated with several life-threatening complications. Hepatic encephalopathy remains to be one of the most debilitating complication of liver cirrhosis. The occurrence of hepatic encephalopathy may be directly related to endogenous worsening of liver function or occurs in the presence of specific precipitating factor. Infection such as urinary tract infection is a common precipitant of hepatic encephalopathy. We present a case of 66 year old female with recurrent hepatic encephalopathy in hepatitis B-related liver cirrhosis precipitated by urinary tract infection. Rapid and precise recognition of precipitating factor in hepatic encephalopathy is very substantial for implementation of preventive measures and optimal treatment plan in order to achieve better outcomes in liver cirrhosis patient.